Gambaran Penerima Transfusi Darah Pada Ruang Rawat Pediatrik di Rumah Sakit Umum Cut Meutia (RSCM) Aceh Utara 2019 2020 - Teuku Ilhami Surya Akbar; Syifa Chairunnisa; Vera Novalia (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract: Giving blood or blood components from a healthy person (donor) to another person is known as blood transfusion. A blood transfusion is intended to save a person's life. The number of blood donors has increased in the last decade, but it is still insufficient to meet the demand for blood. According to WHO guidelines, at least 2% of the total population requires blood, but the use of blood in hospitals is currently very limited. Adults receive blood transfusions more frequently than children and neonates. In adults, it is most commonly used in internal medicine, and in children, it is most commonly used in cases of thalassemia. The purpose of this study is to identify the characteristics of patients receiving transfusions in the pediatric ward at Cut Meutia General Hospital in North Aceh in 2019-2020. The descriptive method was used in the research. Total sampling was used in this study, thedata taken from the patient's medical records at the North Aceh Hospital in 2019-2020 obtaining 89 samples. The study's results for transfusion recipients were frequently found in male sex (55.1%), at 5 years - 11 years (38.2%), blood type O (51.7%) frequentlywith rhesus positive (98.9%). Thalassemia patients received the majority of blood transfusions (50.0%), and blood components were almost always PRC (98.9%). The conclusions in this study were male blood transfusion recipients, aged 5-11 years, blood type O rhesus positive, diagnosis of thalassemia and blood components used by PRC.